2018
DOI: 10.3386/w24888
|View full text |Cite
|
Sign up to set email alerts
|

Priors rule: When do Malfeasance Revelations Help or Hurt Incumbent Parties?

Abstract: 10587). Our pre-analysis plan was pre-registered with EGAP, and is publicly available at egap.org/registration/760. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 29 publications
6
35
0
Order By: Relevance
“…often neighbors, information diffusion across neighboring precincts could account for the lower effect of information provision in such precincts by reducing differences in behavior between them. However, Arias et al (2019) show that precincts that neighbor treated precincts do not exhibit any changes in voting behavior or a greater likelihood of recalling or acting on information provided to their neighbor. Another possibility is that the discussion of the information induced voters in more-connected networks to acquire further political information.…”
Section: Alternative Interpretationsmentioning
confidence: 83%
See 2 more Smart Citations
“…often neighbors, information diffusion across neighboring precincts could account for the lower effect of information provision in such precincts by reducing differences in behavior between them. However, Arias et al (2019) show that precincts that neighbor treated precincts do not exhibit any changes in voting behavior or a greater likelihood of recalling or acting on information provided to their neighbor. Another possibility is that the discussion of the information induced voters in more-connected networks to acquire further political information.…”
Section: Alternative Interpretationsmentioning
confidence: 83%
“…Various studies have shown that belief updating can drive voting behavior, including in the Mexican context that we study (Arias et al 2019). We instead focus on testing whether information provision can also generate voter coordination.…”
Section: Empirical Implications Of Coordination Within Social Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Work in the Philippines has already documented how mayors take advantage of voter ignorance: by claiming credit for central government projects (Labonne, 2013;Cruz and Schneider, 2017), or by ramping up visible infrastructure projects before the elections (Labonne, 2016). Important work has examined the effects on voter behavior of information on politician performance, attributes and campaign activities, though not campaign promises (Ferraz and Finan, 2008;Chong et al, 2015;Humphreys and Weinstein, 2013;Larreguy et al, 2015;Bidwell et al, 2015;Banerjee et al, 2018;Arias et al, 2018;Dunning et al, forthcoming). Other studies focus on direct appeals to reduce clientelism and vote buying (Vicente, 2014;Hicken et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Chong, De La O, Karlan, and Wantchekon (2014) provide experimental evidence during local elections in Mexico that information decreases incumbent party support but also decreases voter turnout and support for a challenger party. Arias, Larreguy, Marshall, and Querubin (2018) argue that whether voters punish politicians when learning new information on wrongdoings depends on their prior beliefs and how they are updated.…”
Section: Literature Review and Contributionmentioning
confidence: 99%